2018
DOI: 10.1103/physrevb.97.075420
|View full text |Cite
|
Sign up to set email alerts
|

Impact of high-frequency pumping on anomalous finite-size effects in three-dimensional topological insulators

Abstract: Lowering of the thickness of a thin-film three-dimensional topological insulator down to a few nanometers results in the gap opening in the spectrum of topologically protected two-dimensional surface states. This phenomenon, which is referred to as the anomalous finite-size effect, originates from hybridization between the states propagating along the opposite boundaries. In this work, we consider a bismuth-based topological insulator and show how the coupling to an intense high-frequency linearly polarized pu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 66 publications
(82 reference statements)
0
14
0
Order By: Relevance
“…Since the real part of both localization parameters, κ ± , must be positive, the surface states (12) exist only for ε g > 0 (tensile strain). Physically, this means that the existence of the surface states (12), first, arises from the BIA terms (α = 0) and, second, it strongly depends on the sequence order of their parent bulk states, ψ ±1/2 and ψ ±3/2 . To find the dispersion of the surface states (12) for small wave vectors k s , we have to project the total Hamiltonian (1) to the subspace spanned by these two states, {Ψ 1 , Ψ 2 }.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the real part of both localization parameters, κ ± , must be positive, the surface states (12) exist only for ε g > 0 (tensile strain). Physically, this means that the existence of the surface states (12), first, arises from the BIA terms (α = 0) and, second, it strongly depends on the sequence order of their parent bulk states, ψ ±1/2 and ψ ±3/2 . To find the dispersion of the surface states (12) for small wave vectors k s , we have to project the total Hamiltonian (1) to the subspace spanned by these two states, {Ψ 1 , Ψ 2 }.…”
Section: Resultsmentioning
confidence: 99%
“…Physically, this means that the existence of the surface states (12), first, arises from the BIA terms (α = 0) and, second, it strongly depends on the sequence order of their parent bulk states, ψ ±1/2 and ψ ±3/2 . To find the dispersion of the surface states (12) for small wave vectors k s , we have to project the total Hamiltonian (1) to the subspace spanned by these two states, {Ψ 1 , Ψ 2 }. Keeping the terms linear in k s , we arrive at the effective Hamiltonian,…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the Floquet theory that allows one to map a time-dependent problem into a stationary one, it has been shown that a periodic perturbation can induce topological phase transitions in a topological trivial insulator [44][45][46][47][48][49][50][51][52][53][54][55][56][57]. Later the corresponding Floquet topological insulators have been observed by experiments [45,46].…”
Section: Introductionmentioning
confidence: 99%
“…Also, it has been shown that an intense high-frequency linearly polarized light can be used to manipulate the value of a gap in of a non-doped topological insulator thin film [56]. However, the linearly polarized light cannot include the contribution of 1/ω, so that they only estimated the terms proportional to 1/ω 2 [56], where ω is the frequency of the polarized light. Noteworthy, the circularly polarized light can include the contribution of 1/ω.…”
Section: Introductionmentioning
confidence: 99%